Withstanding Vulnerability throughout Adult Life Dynamics of Stressors, Resources, and Reserves - Spini, Dario; Widmer, Eric (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
XXI, 451 p. 19 illus.